Testing of Wood Preservatives - Tewari, M. C.; Pande, J. N .; Purushothau, A. (Indian Forester, 1952)
The wood preservative copper-chrome-boric acid composition which is a modification of the copper-chrome-arsenic composition ( ASCU ) replacing arsenic pentoxide by boric acid, was tested in the laboratory and in the field. These tests indicated that :-(I) thin veneer specimens treated with this preservative were all sound in the test yard after about 2 years. While the untreated ones were all destroyed within 5-10 months; (2) the preservative gets satisfactorily fixed in wood. The following conclusions were, therefore, arrived at :-(I) this preservative cannot be considered as a substitute for ASCU, but can be used in place of Celcure; (2) for treatment of timber for use in dwelling houses and packing cases, it may be preferred to ASCU which is likely to give poisonous arsenic fumes under a fire accident; (3) an absorption of 0.75 to 1.0 lt. per cubic foot for house-building timbers, and 0.5 lt. per cubic foot for packing case timbers, can be expected to give satisfactory protection against attack by fungi and insects including termites and (4) for treatment of poles, piles, etc., it is best to wait till sufficient service data are obtained.